The Effect of Variation Dextrose Equivalents Maltodextrin Values on the Microencapsulant Characteristic of Teak Leaves (Tectona Grandis L.f) Natural Dye - Ernawati, Umi Retno; Khasanah, Lia Umi; Anandito, R. Baskara Katri (Jurnal Teknologi Pertanian, 2014)
This study was conducted to determine the effect of variations dextrose equivalents maltodextrin values (DE 5, DE 15, DE 25) on the microencapsulant characteristic of teak leaves (Tectona grandis L.f) natural dye. This study used a completely randomized design (RAL) with one factors (variations in Dextrose Equivalents Maltodextrin values) with 3 levels  (DE 5, DE 15, DE 25). The results were compared to teak leaves extract and teak leaves powder dye without coating. The observation was conducted on specimen is randemen, total anthocyanin content, free radicals scavenging activity, the quality of the color (L*a*b, 0Hue), moisture content, solubility in water, microstructure and solvent residue (ethanol). The variations dextrose equivalents  values of maltodextrin (DE 5, DE 15, DE 25) affected the microencapsulant characteristics of teak leaves natural dyes (Tectona grandis L. f .) In terms of randemen, total anthocyanin content, free radical activity arrests, quality color (L*a*b, 0Hue), moisture content, solubility, microstructure and solvent residue (ethanol). The Increasing dextrose equivalents value of maltodextrin increased specimen randemen, free radicals scavenging activity, quality of the color ( L* a* b, 0Hue ), moisture content, solubility in water and solvent residue (ethanol) of teak leaves natural dyes mikroencapsulant. However, the increasing dextrose equivalent value of maltodextrin lead to decreasing total anthocyanins content of teak leaves natural dyes mikroencapsulant. Maltodextrin with a dextrose equivalents values of 15 ​​produced microstructure of teak leaves natural dye with the best characteristics. The resulting microencapsule was expected to be applied in food as natural dye.Keywords : Dextrose equivalents (DE), Maltodextrine, Mikroencapsulant, Natural Dyes